2014
DOI: 10.1007/s10072-014-1628-5
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid, morin inhibits oxidative stress, inflammation and enhances neurotrophic support in the brain of streptozotocin-induced diabetic rats

Abstract: Diabetes-induced damages in brain are known as diabetic encephalopathy, which is well characterized by cellular, molecular and functional changes in the brain of diabetic subjects and rodents. However, little is known about the mechanism of damages and the therapeutic strategies in ameliorating those damages in the diabetic brain. In this study, we utilized a flavonoid, morin which is emerging as a potent drug against a wide range of free radical-mediated as well as neurodegenerative diseases. Morin (15 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 24 publications
5
37
0
1
Order By: Relevance
“…Another purpose of the study was to determine the therapeutic efficiency of resveratrol which might be effective against oxidative stress and enhance the antioxidant systems to protect brain tissues from diabetes induced pathologies. Several in vitro, experimental, and clinical studies have suggested that one of the reasons for diabetic neuronal degeneration is the oxidative stress generated by elevated glucose levels (El-Akabawy & El-Kholy, 2014; Mushtaq et al, 2014; Ola et al, 2014). Our results demonstrated a Figure 1.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another purpose of the study was to determine the therapeutic efficiency of resveratrol which might be effective against oxidative stress and enhance the antioxidant systems to protect brain tissues from diabetes induced pathologies. Several in vitro, experimental, and clinical studies have suggested that one of the reasons for diabetic neuronal degeneration is the oxidative stress generated by elevated glucose levels (El-Akabawy & El-Kholy, 2014; Mushtaq et al, 2014; Ola et al, 2014). Our results demonstrated a Figure 1.…”
Section: Discussionsupporting
confidence: 77%
“…Oxidative stress markers in diabetic rat brain tissues measured in control, diabetic, resveratrol supplemented control (C+RSV), and resveratrol supplemented diabetic (D+RSV) groups. El-Kholy, 2014; Jing et al, 2013;Mushtaq et al, 2014;Ola et al, 2014). However, the exact mechanisms of how diabetes could affect memory functions remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we observed that flavonoid morin ameliorated the level of neurotrophic factor in central and peripheral nervous system of diabetic rat. 32,49 Thus, it is likely that antioxidant potential of flavonoid, NG may improve neurotrophic factors, which in turn might protect sciatic nerve damage in diabetic rats. Furthermore, our results are supported by histological features of sciatic nerve sections from NG-treated diabetic groups, which revealed a decrease in degenerated bodies and preservation of sciatic nerve architecture.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in the presence of nitric oxide, superoxide can react with nitric oxide to form peroxynitrite [192,193], a highly reactive species that is known to exert cytotoxicity via modification of macromolecules [194][195][196] implicated in diabetes [197][198][199][200][201]. Given the role of oxidative stress in diabetes, a variety of antioxidants and phytochemicals have been evaluated for their protective or preventive effects on diabetes and its complications [202][203][204][205][206][207][208][209][210][211].…”
Section: Oxidative Stressmentioning
confidence: 99%